Acquisition of Language, Linguistics Via Computer (AI) in Higher Education Institutions and Its Effects - Mammadova, Banovsha Guloglan; Aliyeva, Leyla Isa; Mammadova, Minavvar; Aliyeva, Ruhangiz Mammad; Narayanam, Venkata Siva Kumari; Baghirzadeh, Zuleykha Murad; Allahverdiyeva, Lala Zahir; Mirzayev, Elchin; Mehdiyeva, Gunel Vilayat Bayramova; Aliyeva, Saadat Jahangir; Ahmadzadeh, Tamilla Ramin (Forum for Linguistic Studies, 2025)
The ever-evolving realm of higher education offers revolutionary prospects for educators and learners through the merging of language studies, linguistics, and artificial intelligence (AI). This paper examines the interdisciplinary integration of these fields, highlighting their combined capacity to improve teaching methods, research innovation, and educational results in higher education institutions. The study initiates by analyzing conventional methods of language and linguistics instruction, pinpointing enduring pedagogical issues like student engagement, assessment precision, and linguistic diversity. It subsequently examines the transformative influence of AI technologies—such as natural language processing (NLP), machine learning, speech recognition, and automated evaluation—in tackling these issues. The paper illustrates how AI-powered technologies may customize learning, support multilingual education, and enhance linguistic research through a comprehensive examination of existing literature, theoretical frameworks, and case studies.